Sosialisasi Content Marketing Untuk Pemula Dalam Mengembangkan Usaha Bagi Mahasiswa Administrasi Bisnis - Yusi Irensi Seppa; Siti Syarifah Wafiqah Wardah; Maya Kasmita; Andi Muhammad Rivai; Dyan Paramitha Darmayanti (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The success of a business really depends on how it is managed, the innovations and modifications made so that the products or services offered can continue to compete and become the choice of customers and one of these can be realized by using Content Marketing. This Community Service aims to provide knowledge and understanding to Business Administration Study Program students regarding Content Marketing for Beginners in developing businesses. This service activity focuses on Content Marketing Socialization material for Beginners in Developing Businesses for Business Administration Students, especially Class of 2023 students, Faculty of Social Sciences and Law, Makassar State University. From the results of this evaluation, it can be seen that the majority of socialization participants strongly agree with the evaluation results of socialization activities and can feel the benefits very well. Understanding the optimal use of Content Marketing for Beginners in Developing a Business will provide benefits for students.